The effect of a health education package on the health-seeking behavior of TB symptomatic urban poor residents. - Simbulan, Nymia P. (2000)
The study focused on the effects of a health education intervention package on the health-seeking behavior, TB knowledge and attitudes of TB symptomatic urban poor residents. Specifically, it aimed to: 1) compare the different characteristics like socio-demographic, nature of TB experience, self-perception, etc, of TB symptomatics known and unknown, 2) identify the different types of health-seeking behaviors related to TB of TB symptomatics known and unknown, 3) identify the factors associated with health-seeking behavior related to TB of the TB symptomatics known and unknown, 4) ascertain the effects of health education intervention package on the health-seeking behavior, i.e.going for sputum examination, knowledge and attitudes on TB, of the TB symptomatics unknown, and 5) design a model to predict the health-seeking behavior specifically going for sputum examination of TB symptomatics unknown. A combination of quantitative and qualitative data-collection techniques was used in this quasi-experimental study. A total of 182 TB symptomatics from the two barangays in Navotas were classified into the experimental group or those who participated in the health education intervention package and the control group or those who did not receive the intervention. The study has established the positive impact of a health education package on sputum examination, TB knowledge and attitudes of the TB symptomatics. It has identified education, perceived vulnerability, self-efficacy, health locus of control, TB attitudes and the interaction term gender and health intervention as significant predictors of the health-seeking behavior, i.e. sputum examination. Concomitantly, the variables gender, TB symptoms experienced, health-seeking behavior, satisfaction with health center services, social support, self-efficacy, overall TB knowledge and knowledge on diagnosis and treatment were found to be strongly associated with TB status. Moreover, the study findings revealed that the form of health-seeking behavior prevalent among the TB symptomatics unknown was self-medication while it was consultation at the health center for the TB known. On the basis of the study findings, the following recommendations were made: 1) adapt the TB health education intervention package developed and implemented in this study with TB symptomatics, in general, and women, in particular, as principal target participants. 2) design the TB health education package focusing on the predictors of sputum examination identified in the study, such as perceived vulnerability, self-efficacy, health locus of control and attitudes toward TB. 3) develop IEC materials for the TB health education intervention package which are gender-sensitive, instructive, simple and with illustrations or drawings. This also includes improving their distribution to barangay health centers where they are most needed. 4) enhance the interpersonal skills of health providers especially at the local level to more effectively handle and deal with a broad spectrum of clients. 5) strengthen collaboration and coordination between local public health providers and private health professionals in the community. 6) expand the category of patients given priority in the distribution of anti-TB drugs in barangay health centers to include not only those with 2 smear positive specimens but also those with one smear positive specimen or those with smear-negative results but have cavitary pulmonary lesions based on chest x-ray results. 7) duplicate this study in other urban poor areas in Metro Manila to validate the preliminary results, primarily the predictors of sputum examination identified.
Thesis (DrPH, Health Education)--University of the Philippines, Manila
Keywords: Tuberculosis; Health-seeking behavior